2012
DOI: 10.1172/jci57256
|View full text |Cite
|
Sign up to set email alerts
|

An anti-diabetes agent protects the mouse brain from defective insulin signaling caused by Alzheimer’s disease–associated Aβ oligomers

Abstract: Defective brain insulin signaling has been suggested to contribute to the cognitive deficits in patients with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

28
670
0
9

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 741 publications
(720 citation statements)
references
References 77 publications
28
670
0
9
Order By: Relevance
“…Similarly, treatment of patients with type 2 diabetes and islet recipients with type 1 diabetes, at early stages of beta cell dysfunction may slow down the process of hIAPP aggregation and thereby amyloid-induced beta cell death. In support, two recent studies have demonstrated that treatment with GLP-1R agonists, such as exenatide and liraglutide, reduces Aβ oligomers, amyloid plaque formation and toxicity in the brains of mice in models of Alzheimer's disease [47,48].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Similarly, treatment of patients with type 2 diabetes and islet recipients with type 1 diabetes, at early stages of beta cell dysfunction may slow down the process of hIAPP aggregation and thereby amyloid-induced beta cell death. In support, two recent studies have demonstrated that treatment with GLP-1R agonists, such as exenatide and liraglutide, reduces Aβ oligomers, amyloid plaque formation and toxicity in the brains of mice in models of Alzheimer's disease [47,48].…”
Section: Discussionmentioning
confidence: 77%
“…We further demonstrated that exenatide-treated islets had markedly lower levels of beta cell phospho-JNK, suggesting that exenatide may protect islet beta cells from amyloid toxicity by reducing JNK activation. Interestingly, elevated JNK phosphorylation and prevention of its activation by exenatide were recently reported in a mouse model of Alzheimer's disease [48], raising the idea that different forms of amyloidogenesis share similar mechanisms of toxicity.…”
Section: Discussionmentioning
confidence: 98%
“…There is a strong link between diabetes, insulin resistance in the brain, and AD (24)(25)(26)(27). Loss of insulin action in the brain also causes increased phosphorylation of tau protein, an early marker of AD (26).…”
Section: Discussionmentioning
confidence: 99%
“…This pathological change is likely to emerge before Aβ42 accumulation (Chua et al ., 2011). In agreement with previous findings in animal models and patients (Bomfim et al ., 2012; Talbot et al ., 2012), significantly reduced brain expression of IRβ and AKT and increased level of inactive IRS1 (IRS1 pS636 and IRS1 pS612) were found in the APP/PS1 mice used here. This indicates that the brain insulin signaling pathway is already compromised in 6‐month‐old APP/PS1 mice.…”
Section: Discussionmentioning
confidence: 99%
“…Serine phosphorylation in IRS1 (IRS1pSer) has been found in the brain of the APP/PS1 transgenic mouse model and in hippocampi of cynomolgus monkeys receiving i.c.v. injections of Aβ oligomers (Bomfim et al ., 2012). Inhibitory IRS1pSer can block downstream insulin signaling (Zhao et al ., 2008b).…”
Section: Discussionmentioning
confidence: 99%